Against the Flow: Islamic Trauma and the Reinterpretation of Musso in Indonesian Literature - Santoso, Joko (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
The 1965 events involving the Indonesian Communist Party (PKI) are considered one of the greatest human catastrophes in Indonesia. However, the 1948 Madiun PKI uprising also represents a significant historical moment. In 1965, the PKI became associated with victimhood, particularly in relation to the mass killings, while in 1948, the PKI was cast as the perpetrator of violence. This article examines two literary works that address the PKI’s 1948 involvement: Tentang Kamu by Tere Liye and Ayat-Ayat yang Disembelih by Anab Afifi and Thowaf Zuharon. Using Marianne Hirsch’s postmemory theory, the study explores how these narratives construct an Islamic counter-memory, framing the PKI as a source of trauma for the second generation of Indonesian Muslims. One strategy, termed